Treatment of Chagas cardiomyopathy. - Botoni, Fernando Antônio (2013)
Chagas’ disease (ChD), caused by the protozoa Trypanosoma cruzi (T. cruzi), was discovered and described by the Brazilian physician Carlos Chagas in 1909. After a century of original description, trypanosomiasis still bringsmuch misery to humanity and is classified as a neglected tropical disease prevalent in underdeveloped countries, particularly in South America. It is an increasing worldwide problem due to the number of cases in endemic areas and the migration of infected subjects tomore developed regions, mainly North America and Europe. Despite its importance, chronic chagas cardiomyopathy (CCC) pathophysiology is yet poorly understood, and independently of its social, clinical, and epidemiological importance, the therapeutic approach of CCC is still transposed from the knowledge acquired from other cardiomyopathies. Therefore, the objective of this review is to describe the treatment of Chagas cardiomyopathy with emphasis on its peculiarities.